2015
DOI: 10.1175/jhm-d-14-0217.1
|View full text |Cite
|
Sign up to set email alerts
|

The Flashiest Watersheds in the Contiguous United States

Abstract: The authors identify the flashiest watersheds in the contiguous United States based on frequency of discharge peaks exceeding 1 m3 s−1 km−2. The entire digitized record of USGS instantaneous discharge data is used for all stream gauging stations with over 10 years of data. Using the 1 m3 s−1 km−2 threshold, the flashiest basins in the contiguous United States are located in urban areas along a swath of states from the south-central United States to the mid-Atlantic and in mountainous areas of the West Coast, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 51 publications
6
58
1
Order By: Relevance
“…Watersheds with lower average slopes are expected to exhibit more variability in the saturated zone and from subsurface throughflow, which result in a VSA response (Dunne et al ., ). Smaller basins are likely to exhibit flashier hydrological response, which may be associated with reduced VSA effects (Smith and Smith, ). The meteorological control included was the average total annual precipitation in the watershed.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…Watersheds with lower average slopes are expected to exhibit more variability in the saturated zone and from subsurface throughflow, which result in a VSA response (Dunne et al ., ). Smaller basins are likely to exhibit flashier hydrological response, which may be associated with reduced VSA effects (Smith and Smith, ). The meteorological control included was the average total annual precipitation in the watershed.…”
Section: Methodssupporting
confidence: 89%
“…Developed open space in the National Land Cover Dataset is defined as development that is less than 20% impervious, so these areas could still contain roads and drainage infrastructure that increase hydraulic connectivity. Urban pervious surfaces could have very little storage because of compaction and localized subsurface saturation because of lawn watering and leakage and therefore lead to saturation overflow conditions even during very small events (Bhaskar and Welty, ; Lerner, ; Smith and Smith, ). Although this process is physically more similar to Dunne's VSA concept of saturation overland flow, if storage is minimal, the hydrological response at this level of analysis is indistinguishable from Hortonian overland flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The West Coast is characterized by high erosion rates (average long-term erosion rate = 336 mm/kyr, and has a Mediterranean climate with dry, warm summers and mild, wet winters (Hirschboeck, 1991). Rivers in the Mid-Atlantic Appalachians and along the West Coast tend to experience a substantial number of "flashy" storms (Smith & Smith, 2015). Floods result from early autumn tropical cyclones, wintertime "nor'easters," and, occasionally, intense summer thunderstorms (Hirschboeck, 1991).…”
Section: Site Selectionmentioning
confidence: 99%
“…Many studies have detailed the increase in flood volumes and discharge peaks associated with increasing impervious area (for example, [3][4][5][6][7]). A national study found that the flashiest watersheds in the country are urban [8]. The U.S. is urbanizing as the population continues to move into cities and suburbs.…”
Section: Introductionmentioning
confidence: 99%